2020
DOI: 10.1136/esmoopen-2020-000953
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the aggressiveness of care at the end of life for patients with cancer dying in hospital: a nationwide retrospective cohort study in mainland Portugal

Abstract: IntroductionThere is growing concern about the aggressiveness of cancer care at the end of life (ACCEoL), defined as overly aggressive treatments that compromise the quality of life at its end. Recognising the most affected patients is a cornerstone to improve oncology care. Our aim is to identify factors associated with ACCEoL for patients with cancer dying in hospitals.MethodsAll adult patients with cancer who died in public hospitals in mainland Portugal (January 2010 to December 2015), identified from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As for the administration of intravenous chemotherapy during the last 2 weeks of life, the results in our cohort (5.4%) appeared reasonable and comparable with other European data. 30 Besides, no significant variability was observed between treatment centres in Belgium.…”
Section: Discussionmentioning
confidence: 94%
“…As for the administration of intravenous chemotherapy during the last 2 weeks of life, the results in our cohort (5.4%) appeared reasonable and comparable with other European data. 30 Besides, no significant variability was observed between treatment centres in Belgium.…”
Section: Discussionmentioning
confidence: 94%
“…The use of chemotherapy at end-of-life, particularly in the last month, is considered an aggressive measure and should be avoided [5]. One of the largest studies in Portugal to assess the factors associated with the aggressiveness of end-of-life care [6], revealed that advanced age, breast cancer and metastatic disease are associated with a lower risk of aggressiveness, while the existence of other comorbidities, gastrointestinal and hematological neoplasms were considered risk factors in this context. This study also showed that, in Portugal, 7 out of 10 patients with cancer in the end of life stage were subjected to some type of aggressiveness in the care provided, such as chemotherapy treatments in the last month of life, a higher number of hospitalization episodes and higher number of deaths in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…This reality of excessive use of technology has contributed to the dehumanization of health care provision, namely the use of disproportionate means of treatment and diagnosis in terminally ill patients [9]. In a retrospective study (2010-2015) involving 92,155 cancer patients in hospital units in Portugal published in 2020 in the journal European Society for Medical Oncology Open, the authors reported a 71% prevalence of aggressive end-of-life care [10].…”
Section: Technological Advances Vs Life Prolongationmentioning
confidence: 99%
“…In this line of thought, we believe it is pertinent to reflect on a subject that, in our opinion, is somewhat hidden, but which is relevant in bioethics: dysthanasia. We believe that more than the discussion on euthanasia that has overflowed in recent years into the newspaper headlines, the practice of using all diagnostic/therapeutic means available to prolong lives by a thread, postponing death, is an act still very present in hospitals [9][10][11][12][13][14]. Despite this evidence, this debate "…has in large part been neglected, not only in treatment decisions at the bedside but in public discussions-comfort care-the physician's obligation to alleviate suffering, enhance well being and support the dignity of the patient in the last few days of life" [15].…”
Section: Technological Advances Vs Life Prolongationmentioning
confidence: 99%